FRI0021 Synovial Explant Activity is Associated with Disease Activity in Biologically Treated Rheumatoid Arthritis Patients: A Cohort Study. (10th June 2014) - Andersen, M.; Boesen, M.; Ellegaard, K.; Christensen, R.; Söderström, K.; Søe, N.; Spee, P.; Mørch, U.G.; Torp-Pedersen, S.; Bartels, E.M.; Danneskiold-Samsøe, B.; Vendel, N.; et al.
Abstract : Background: Remission is only achieved in part of rheumatoid arthritis (RA) patients treated with synthetic disease modifying anti-rheumatic drugs, sDMARDs. The increasing number of available biologic DMARDs (bDMARDs) challenges treatment decision making. Patient tailored treatment approaches may provide a solution for the future bDMARD treatment strategies. Objectives: To investigate whether changes in explant pro-inflammatory mediator production would be associated with changes in colour Doppler ultrasound (CDUS), magnetic resonance imaging (MRI) and disease activity score of 28 joints (DAS-28) in a RA cohort scheduled for bDMARD treatment. Methods: 16 RA patients scheduled for bDMARD treatment were evaluated by Color Doppler ultrasound and 3 Tesla magnetic resonance imaging (MRI) and then synovectomised of the hand joints by a needle athroscopic procedure. Synovial tissue cultures (40 samples) were established from the synovectomy material and incubated for two weeks with the specific bDMARD prescribed for treatment of the individual patient. The spontaneous, isotype control and bDMARD treated synovial explant production of interleukin 6 (IL-6), monocyte chemoattractive protein 1 (MCP-1) and macrophage inflammatory protein 1 beta (MIP-1b) were compared with the changes in clinical and imaging variables after a minimum of three months' bDMARD treatment. Change in imaging pathology was defined as change in: colour Doppler activity, synovitis score, bone marrow oedema (BME) score and erosion score using the RA MRI score (RAMRIS) score. Spearman rank correlations were calculated for outcome measures using averaged values from the various explant positions. To handle repeated measures from multiple sample from the same patients we applied a mixed linear model was for the statistical analyses for calculation of the associations of explant activity with imaging data; a p-value<0.05 was considered statistically significant. Results: After a median of 7 (Interquartile range: 4.9; 9.0) months bDMARD treatment explant fold changes in IL-6 were significantly associated changes in CDUS (r =0.68; MIXED model: p=0.04) and RAMRIS BME (r=0.56; MIXED model: p=0.03). Explant fold change of MCP-1 was significantly associated to the change of RAMRIS BME score (r.=0.49; MIXED model: p=0.01). No statistically significant associations were seen with regards to changes in MIP-1b production, isotype controls, DAS-28 or RAMRIS erosion scores. Conclusions: Changes in IL-6 and MCP-1 produced by RA synovial explants obtained prior to initiation of bDMARD treatment were associated with the subsequent in vivo responses to the specific bDMARD used. Thus, synovial explants may have a potential for development of a patient tailored treatment approach (i.e., personalised medicine). Acknowledgements: Supported by unrestricted grants from Novo Nordisk and the Oak Foundation. Disclosure of Interest: M. Andersen Employee of: Nono Nordisk, M. Boesen: None declared, K. Ellegaard: None declared, R. Christensen: None declared, K. Söderström Employee of: Nono Nordisk, N. Søe: None declared, P. Spee Employee of: Nono Nordisk, U. Mørch Shareholder of: Nono Nordisk, Employee of: Nono Nordisk, S. Torp-Pedersen: None declared, E. Bartels: None declared, B. Danneskiold-Samsøe: None declared, N. Vendel: None declared, L. Karlsson Employee of: Nono Nordisk, H. Bliddal Grant/research support: Nono Nordisk DOI: 10.1136/annrheumdis-2014-eular.4661